Labour Market Integration and the Transition to Parenthood: A Comparison of Germany and the UK - Christian Schmitt (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
The aim of this paper is to investigate the hypothesis that after leaving the educational system, labour market integration has a causal effect on first-birth decisions. The analysis focuses on two major research questions: First, how is the timing of first parenthood associated with previous labour market performance? Second, can differences in first birth-risks be related to labour market performance? In other words, to what extent do the fertility decisions of successfully integrated individuals differ from those who are poorly integrated into the labour force? To account for the impact of cross-national differences in institutional settings, I contrast the continental conservative German welfare state with the liberal market economy of the UK. To account for gender-specific differences in opportunity costs, I distinguish between men and women in this analysis. Using longitudinal micro-data from the SOEP and BHPS, I apply a piecewise constant exponential hazard model. The results show a significantly reduced first-birth risk in the case of German men with weak occupational integration, as well as in the case of British and German women with pronounced labour market attachment. Furthermore, regarding the timing of family formation, a lengthy process of occupational integration tends to delay the transition to parenthood for both men and women, especially in Germany.
Keywords: 330; Fertilty; first-birth; occupational integration; cross-national comparison